Engineering Natural Pollen Grains as Multifunctional 3D Printing Materials. (25th August 2021) - Chen, Shengyang; Shi, Qian; Jang, Taesik; Ibrahim, Mohammed Shahrudin Bin; Deng, Jingyu; Ferracci, Gaia; Tan, Wen See; Cho, Nam‐Joon; Song, Juha
Abstract: The development of multifunctional 3D printing materials from sustainable natural resources is a high priority in additive manufacturing. Using an eco‐friendly method to transform hard pollen grains into stimulus‐responsive microgel particles, we engineered a pollen‐derived microgel suspension that can serve as a functional reinforcement for composite hydrogel inks and as a supporting matrix for versatile freeform 3D printing systems. The pollen microgel particles enabled the printing of composite inks and improved the mechanical and physiological stabilities of alginate and hyaluronic acid hydrogel scaffolds for 3D cell culture applications. Moreover, the particles endowed the inks with stimulus‐responsive controlled release properties. The suitability of the pollen microgel suspension as a supporting matrix for freeform 3D printing of alginate and silicone rubber inks was demonstrated and optimized by tuning the rheological properties of the microgel. Compared with other classes of natural materials, pollen grains have several compelling features, including natural abundance, renewability, affordability, processing ease, monodispersity, and tunable rheological features, which make them attractive candidates to engineer advanced materials for 3D printing applications. Abstract : A pollen‐based microgel suspension is developed that is useful for additive manufacturing and serves multiple functions as follows: 1) functional reinforcement for composite hydrogel inks; and 2) supporting matrix for freeform 3D printing. The use of pollen grains has several advantages such as natural abundance, renewability, affordability, processing ease, monodispersity, and tunable rheological features.